Penerapan TTS (Teka-Teki Silang) Pada Buku Ajar Budi Pekerti Kelas II di Sekolah Dasar Negeri 04 Kubang Putiah - Zarury, Ibnati; Monia, Fenny Ayu; Z, Zuriyati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This Field Experience Practice (PPL) aims to gain experience related to teacher studies, in order to fulfill one of the subjects of the Islamic Religious Education Bachelor's program at Sjech Djamil Djambek Bukittinggi State Islamic University and provide students with knowledge and even experience in the world of education. Regarding an educational process carried out at SDN 04 Kubang Putiah as an effort to increase learning in terms of students' interest in participating in the learning process, in this case the time is more or less between 22 August - 10 November 2023 which follows the independent curriculum-based learning process at SDN 04 Kubang Putiah. In the implementation of the educational program carried out, in class II a TTS (crossword puzzle) based learning system is implemented within the scope of Islamic Religious Education which refers to the character textbook for class II elementary school. The implementation starts from the approach, explanation of material, direction and implementation of the learning system which is carried out in accordance with the TTS system that has been designed. Field Experience Practice (PPL) was carried out at SD Negeri 04 Kubang Putiah. Jl. Raya Kubang Putiah, Kubang Putiah, Kec. Banuhampu, Kab. Agam, Prov. West Sumatra. In its application, results were obtained in the development of learning that had variations and enabled students to increase their focus and increase their intellectual value in learning.